Construction of an Immunotoxin, D2C7-(scdsFv)-PE38KDEL, Targeting EGFRwt and EGFRvIII for Brain Tumor Therapy - Vidyalakshmi Chandramohan; Xuhui Bao; Stephen T. Keir; Charles N. Pegram; Scott E. Szafranski; Hailan Piao; Carol J. Wikstrand; Roger E. McLendon; Chien‐Tsun Kuan; Ira Pastan; Darell D. Bigner (2013)
The EGF receptor gene (EGFR) is most frequently amplified and overexpressed, along with its deletion mutant, EGFRvIII, in glioblastoma. We tested the preclinical efficacy of the recombinant immunotoxin, D2C7-(scdsFv)-PE38KDEL, which is reactive with a 55-amino acid (AA) region present in the extracellular domain of both EGFRwt (583-637 AAs) and EGFRvIII (292-346 AAs) proteins.The binding affinity and specificity of D2C7-(scdsFv)-PE38KDEL for EGFRwt and EGFRvIII were measured by surface-plasmon resonance and flow cytometry. In vitro cytotoxicity of D2C7-(scdsFv)-PE38KDEL was measured by inhibition of protein synthesis in human EGFRwt-transfected NR6 (NR6W), human EGFRvIII-transfected NR6 (NR6M), EGFRwt-overexpressing A431-epidermoid-carcinoma, and glioblastoma xenograft cells (43, D08-0493MG, D2159MG, and D270MG). In vivo antitumor efficacy of D2C7-(scdsFv)-PE38KDEL was evaluated using 43, NR6M, and D270MG orthotopic tumor models.The KD of D2C7-(scdsFv)-PE38KDEL for EGFRwt and EGFRvIII was 1.6×10(-9) mol/L and 1.3×10(-9) mol/L, respectively. Flow cytometry with NR6W and NR6M cells confirmed the specificity of D2C7-(scdsFv)-PE38KDEL for EGFRwt and EGFRvIII. The D2C7-(scdsFv)-PE38KDEL IC50 was 0.18 to 2.5 ng/mL on cells expressing EGFRwt (NR6W, A431, 43, and D08-0493MG). The D2C7-(scdsFv)-PE38KDEL IC50 was approximately 0.25 ng/mL on EGFRvIII-expressing cells (NR6M) and on EGFRwt- and EGFRvIII-expressing glioblastoma xenograft cells (D2159MG and D270MG). Significantly, in intracranial tumor models of 43, NR6M, and D270MG, treatment with D2C7-(scdsFv)-PE38KDEL by convection-enhanced delivery prolonged survival by 310% (P=0.006), 28% (P=0.002), and 166% (P=0.001), respectively.In preclinical studies, the D2C7-(scdsFv)-PE38KDEL immunotoxin exhibited significant potential for treating brain tumors expressing EGFRwt, EGFRvIII, or both.